Knowledge, Perception and Attitude among Dental Students on the Use of Online Education in a Higher Institution of Learning (HEI) - Ronald Cabral; Garcia PD; Aquinaldo JT; Barongan DG; Besweng MG S; Padlan E (Asian Journal of Healthcare Analytics, 2023)
This study aims to examine and identify the knowledge, perception, and attitude of dental students towards online education in higher institution of learning. Online education is an electronically supported learning that relies on the internet for teacher/student interaction and the distribution of class materials. Assessment of knowledge, perception, attitudes, and readiness of 3rd year to 6th year dental students at Lyceum Northwestern university toward the challenges of online learning in dental education was done through electronic questionnaires. Ethical approval was secure from the UREB of the university. The study found that the dental students who participated had a good understanding of online coursework and were proficient in computer skills. The success of e-learning is largely dependent on technological accessibility and having a stable internet connection. However, respondents expressed reservations about the quality of the learning process compared to traditional face-to-face classroom learning. The respondents felt that a combination of both traditional teaching methods and online tutorials would be more ideal than either method alone.